2023
DOI: 10.1021/acs.molpharmaceut.2c00895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gastric pH Variations on the Release of Amorphous Solid Dispersion Formulations Containing a Weakly Basic Drug and Enteric Polymers

Abstract: Enteric polymers are widely used in amorphous solid dispersion (ASD) formulations. The aim of the current study was to explore ASD failure mechanisms across a wide range of pH conditions that mimic in vivo gastric compartment variations where enteric polymers such as hydroxypropyl methylcellulose phthalate (HPMCP) and hydroxypropyl methylcellulose acetate succinate (HPMCAS) are largely insoluble. Delamanid (DLM), a weakly basic drug used to treat tuberculosis, was selected as the model compound. Both DLM free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 71 publications
(171 reference statements)
1
33
0
Order By: Relevance
“…The initial steep increase in polymer dissolution rate as the buffer capacity increases is readily explained by eq and the pH-dependent solubility of HPMCAS. The p K a of HPMCAS-MF has been reported as 4.92 or 5.0, , and Nguyen et al reported that the solubility of HPMCAS-MF increased steeply between pH 5.0 and 6.5 (no values above pH 6.5 were reported) . Therefore, it is probable that, for a bulk pH of 6.8, a lower pH exists at the polymer-solution interface due to release of protons following polymer ionization, which serves to decrease the polymer solubility and reduce polymer flux as per eq .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial steep increase in polymer dissolution rate as the buffer capacity increases is readily explained by eq and the pH-dependent solubility of HPMCAS. The p K a of HPMCAS-MF has been reported as 4.92 or 5.0, , and Nguyen et al reported that the solubility of HPMCAS-MF increased steeply between pH 5.0 and 6.5 (no values above pH 6.5 were reported) . Therefore, it is probable that, for a bulk pH of 6.8, a lower pH exists at the polymer-solution interface due to release of protons following polymer ionization, which serves to decrease the polymer solubility and reduce polymer flux as per eq .…”
Section: Discussionmentioning
confidence: 99%
“…The pK a of HPMCAS-MF has been reported as 4.92 or 5.0, 12,67 and Nguyen et al reported that the solubility of HPMCAS-MF increased steeply between pH 5.0 and 6.5 (no values above pH 6.5 were reported). 67 Therefore, it is probable that, for a bulk pH of 6.8, a lower pH exists at the polymer-solution interface due to release of protons following polymer ionization, which serves to decrease the polymer solubility and reduce polymer flux as per eq 2. A surface pH that is lower than the bulk pH has been reported for poorly water-soluble weakly acid drugs when the buffer pH increases beyond 6, where models of pH gradients show that greater deviations between bulk and surface pH occur for lower buffer capacity solutions.…”
Section: Discussionmentioning
confidence: 99%
“…30,51−53 The release extent variation has been rationalized based on the pH-dependent solubility of the basic drug, 51−53 while the matrix surface crystallization under low pH conditions likely reflects the reduced ability of the polymer to act as a crystallization inhibitor at a lower pH when in un-ionized form. 30 Based on the screening data of crystallization inhibition effectiveness, HPMCAS-HF was the only realistic polymeric candidate for formulating ASDs of PTM. Downsides of this particular polymer are its high reported threshold dissolution pH of >6.5 35 and a relatively hydrophobic chemistry, which in combination may lead to slow and incomplete drug release in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was successful for PTM with HPMCAS-HF, yielding ASDs that were physically stable under ambient conditions for several months (Figure S12), in comparison to neat amorphous drug, which crystallized within a few minutes under the same conditions (Figure S2). However, recent studies have highlighted that solid-state stability and solution crystallization studies may not adequately predict the complex landscape of phase transitions that can occur in in vitro conditions that mimic gastrointestinal transit. ,, This has led to the increased utilization of more complex in vitro testing conditions, including two-stage dissolution, where the ASD is first evaluated under conditions simulating gastric media, followed by transfer to fluids simulating intestinal conditions. , In particular, it has been recently highlighted that immersion in gastric conditions, where enteric polymers such as HPMCAS are insoluble, can yield insights into important patterns of phase behavior . Thus, for weakly basic drugs formulated with an enteric polymer, it has been noted that the gastric pH influences both the extent of release from the ASD as well as the tendency of the drug to undergo crystallization on the matrix surface. , The release extent variation has been rationalized based on the pH-dependent solubility of the basic drug, while the matrix surface crystallization under low pH conditions likely reflects the reduced ability of the polymer to act as a crystallization inhibitor at a lower pH when in un-ionized form …”
Section: Discussionmentioning
confidence: 99%
“…The use of a one-stage or two-stage dissolution test may be critically important to detect certain failure mechanisms . Nguyen et al investigated an interesting case study featuring ASDs formulated with various enteric polymers . The pH of the gastric medium influenced the extent of matrix crystallization observed and therefore the final extent of release.…”
Section: Assessment Of Critical Quality Attributesmentioning
confidence: 99%